TOURIST ACTIVITY AND ITS FEATURES AFFECTING THE ORGANIZATION OF MANAGEMENT ACCOUNTING - J. Taktarova; I. Tretyakova (Вестник университета, 2016)
The tourist industry is the most profitable and fast-growing in the world. However the high level of competition in the industry makes the tourist companies to look for new approaches to the development and promotion of tourism product, lower costs, which affects the system of management accounting. In the article the approaches of different authors are considered, the features of tourism activities and are discussed and their shortcomings highlighted. The authors suggests a generalized approach that includes both the features inherent in all services, so the specific characteristics that have only tourist services. This will effectively organize the management accounting in tourism organization.